The contrasting effects of diethylmethylamine during reduction of protons and oxidation of formic acid in diethylmethylammonium-based protic ionic liquids - Goodwin, Sean; Muhammad, Sayyar; Walsh, Darren (Elsevier, 2018)
Ionic liquids are formally defined as liquids that consist entirely of ions, and which are liquid below 100 C. As these liquids are being proposed for use in a range of electrochemical devices and applications, understanding the electrochemical behaviour of these is increasingly important. In this contribution, we describe the effects of parent amine molecules on electrocatalysis in the protic ionic liquids diethylmethylammonium trifluoromethanesulfonate and diethylmethylammonium heptafluorobutanoate. We first show that diethylmethylamine can adsorb onto Pt electrodes during electrocatalytic reduction of trifluoromethanesulfonic acid in diethylmethylammonium trifluoromethanesulfonate. In contrast, diethylmethylamine promotes the oxidation of formic acid in this ionic liquid, by deprotonating the acid to the active formate species. Therefore, the neutral base can either inhibit or enhance electrocatalysis in the liquid, depending on the reaction under consideration. We also show that the mechanism of formic-acid oxidation in diethylmethylammonium heptafluorobutanoate differs significantly from that observed when using diethylmethylammonium trifluoromethanesulfonate. This phenomenon is attributed to adsorption of poisoning spectator species onto the electrode surface, demonstrating that changes to the structure of ionic-liquid anions can have drastic effects on the electrochemistry of these liquids.